Adherence to treatment guidelines for acute diarrhoea in children up to 12 years in Ujjain, India - a cross-sectional prescription analysis - Pathak, Deepali (BioMed Central, 2011)
BACKGROUND: Diarrhoea accounts for 20% of all paediatric deaths in India. Despite WHO recommendations and IAP (Indian Academy of Paediatrics) and Government of India treatment guidelines, few children suffering from acute diarrhoea in India receive low osmolarity oral rehydration solution (ORS) and zinc from health care providers. The aim of this study was to analyse practitioners' prescriptions for acute diarrhoea for adherence to treatment guidelines and further to determine the factors affecting prescribing for diarrhoea in Ujjain, India. METHODS: This cross-sectional study was conducted in pharmacies and major hospitals of Ujjain, India. We included prescriptions from all practitioners, including those from modern medicine, Ayurveda, Homeopathy as well as informal health-care providers (IHPs). The data collection instrument was designed to include all the possible medications that are given for an episode of acute diarrhoea to children up to 12 years of age. Pharmacy assistants and resident medical officers transferred the information regarding the current diarrhoeal episode and the treatment given from the prescriptions and inpatient case sheets, respectively, to the data collection instrument. RESULTS: Information was collected from 843 diarrhoea prescriptions. We found only 6 prescriptions having the recommended treatment that is ORS along with Zinc, with no additional probiotics, antibiotics, racecadotril or antiemetics (except Domperidone for vomiting). ORS alone was prescribed in 58% of the prescriptions; while ORS with zinc was prescribed in 22% of prescriptions, however these also contained other drugs not included in the guidelines. Antibiotics were prescribed in 71% of prescriptions. Broad-spectrum antibiotics were prescribed and often in illogical fixed-dose combinations. One such illogical combination, ofloxacin with ornidazole, was the most frequent oral antibiotic prescribed (22% of antibiotics prescribed). Practitioners from alternate system of medicine and IHPs are significantly less likely (OR 0.13, 95% CI 0.04-0.46, P = 0.003) to prescribe ORS and zinc than pediatricians. Practitioners from 'free' hospitals are more likely to prescribe ORS and zinc (OR 4.94, 95% CI 2.45-9.96, P < 0.001) and less likely to prescribe antibiotics (OR 0.01, 95% CI 0.01-0-04, P < 0.001) compared to practitioners from 'charitable' hospitals. Accompanying symptoms like the presence of fever, pain, blood in the stool and vomiting significantly increased antibiotic prescribing. CONCLUSION: This study demonstrated low adherence to standard treatment guidelines for management of acute diarrhoea in children under 12 years in Ujjain, India. Key public health concerns were the low use of zinc and the high use of antibiotics, found in prescriptions from both specialist paediatricians as well as practitioners from alternate systems of medicine and informal health-care providers. To improve case management of acute diarrhoea, continuing professional development programme targeting the practitioners of all systems of medicine is necessary.